PERAN DINAS PENDIDIKAN KABUPATEN SERANG DALAM MENGIMPLEMENTASIKAN PROGRAM WAJIB BELAJAR 9 (SEMBILAN) TAHUN UNTUK MEMENUHI HAK BELAJAR ANAK - Ade Millatus Sa'adiyyah; Siti Kulsum (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2021)
ABSTRACT This study aims to determine the role of the Serang Regency Education Office in implementing the 9 (nine) year compulsory education program in Serang Banten Regency, to determine the obstacles faced by the Serang Regency Education Office in implementing the 9 (nine) year compulsory education program to fulfill their rights. learning children, and to find out the efforts made by the Serang District Education Office. This study used a descriptive qualitative research method with depiction of facts, data in the form of language expressions and appropriate and systematic interviews. The results of this study indicate that the role of the Serang Dalan district education office in implementing the 9 (nine) year compulsory education program to fulfill children's learning rights has carried out its main duties and functions, namely carrying out regional government affairs in the education sector. So it can be said that the role of the Serang District Education Office is very important in implementing the 9 (nine) year compulsory education program to fulfill children's learning rights. Keywords: Serang District Education Office, 9 (nine) years compulsory education, children's education right. program, fulfilling children's learning rights.